A robust optimization approach for cash flow management in stationery companies. (September 2016) - Righetto, Giovanni Margarido; Morabito, Reinaldo; Alem, Douglas
Highlights: We present an effective optimization approach to support decisions in cash management. The robust model is represented by means of network flows with gains and losses. It considers uncertainty in the parameters that define the financial flows over time. A case study was conducted in the cash flow of a typical stationery company. Several results are presented analyzing the trade-off between risk and return. Abstract: This paper proposes an effective optimization approach based on mixed integer linear programming and robust optimization to support decisions in the cash management problem of stationery companies. The approach represents the problem by means of network flows with gains and losses in an environment with uncertainty in the parameters that define financial flows over time. A case study was conducted in the cash flow of a typical company in the stationery sector with different grace periods and piecewise linear yields. Several results and analysis are presented by applying this robust optimization approach to support the decision maker in relation to the trade-off between risk and return, showing that the approach is able to generate solutions as good as, or better than, the ones of the treasury of the stationery company. It is in these conditions of uncertainty that the motivation of this research can be found, addressing how financial managers project their cash flows in order to maximize their uncertain monetary resources in a given multi-period and finite planning horizon.